The Best of Times, The Worst of Times: Antecedents for and Effectiveness of Community Engagement in Two Small Rural Towns - Liza Pulsipher Wilson; Nick R. Sanyal (The University of Alabama, 2022)
Communities in transition face traumatic change and seek to diversify their economies while continuing to maintain their ties to landscapes that define their heritage. This qualitative case study provides an understanding of community engagement in two transitional towns. Both communities are equally positive about the role of community engagement, but clear differences in the nature and effectiveness of community engagement between the two emerged. The citizens of one town consider their community to have navigated the waters of change. They emulate a bridging community-a diverse group of people with divergent ideas who look outward and toward the future. The second town is still trying to become a place of which residents are proud. They are hindered by the absence of an inspiring leader, the lack of vision, and an inability to communicate between disparate groups. They exemplify a bonding community, where a majority of the citizens have similar mindsets and focus inward.